Laboratory Study on Grout Injection for Improving Subgrade of Airfield Pavements - Goh, Teck Shang; Takashi, Osamu (International Journal of Integrated Engineering, 2014)
This paper shares the authors’ experience of using low pressure grouting to improve the subgrade performance. The first part of the paper introduced a case history where low pressure grouting was applied in weakened subgrade of the active airport pavements in Kuala Lumpur International Airport (KLIA). The treated areas seemed to have been improved and only one of all eight treated areas had reoccurrence of depression. However, the performance of the treated area was difficult to be evaluated. The latter part of the paper investigated the effectiveness of grout injection through laboratory experiments. The laboratory equipment used for the grout injection tests included an injection mold and a steel tank of 1 m length x 0.6 m wide x 0.6 m depth for subgrade soil sample. Three grout types namely neat cement grout, fly ash cement grout, bentonite cement grout were used for this study. Six tests were conducted on sandy soil samples to examine the effect of grout type on the effectiveness of injection. The sandy soil was compacted to approximate 80 % of the maximum dry density. The injection pressure was fixed at 0.5 MPa. Insitu CBR test was also conducted to determine the strength of the grouted sample. The results showed that the fly ash cement grout could penetrate further than the neat cement grout; however its strength was lower than the neat cement grout.